2022
DOI: 10.1101/2022.01.26.477817
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Connectivity dynamics and cognitive variability during aging

Abstract: Aging is accompanied by cognitive changes but strong variations across individuals exists. One of the ways to characterize this individual variability is to use techniques such as magnetoencephalography (MEG) to measure the dynamics of synchronization between brain regions and the variability of this connectivity over time. Indeed, few studies have focused on the fluctuations in the dynamics of brain networks over time and their evolution with age. We therefore used this method on the Cam-CAN database. We show… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…In one of our studies (Jauny et al, 2022 ), we showed that maladaptive changes can be identified in resting-state activity. This study involved the Cam-CAN cohort (e.g., Shafto et al, 2014 ; Taylor et al, 2017 ) and changes in synchrony (with the PLV measure), as well as directed connectivity (with the entropy transfer measure, which provides a directed connectivity measure), were investigated.…”
Section: Normal Agingmentioning
confidence: 62%
See 2 more Smart Citations
“…In one of our studies (Jauny et al, 2022 ), we showed that maladaptive changes can be identified in resting-state activity. This study involved the Cam-CAN cohort (e.g., Shafto et al, 2014 ; Taylor et al, 2017 ) and changes in synchrony (with the PLV measure), as well as directed connectivity (with the entropy transfer measure, which provides a directed connectivity measure), were investigated.…”
Section: Normal Agingmentioning
confidence: 62%
“…Maintenance-related patterns were also observed in healthy older individuals, with a relative absence of impairments in frontoparietal communication dynamics associated with preserved cognitive performance (Rondina et al, 2019 ; Hinault et al, 2020 , 2021 ). The brain's structure-function interplay appears to be at the heart of the heterogeneity associated with maintenance during aging (Courtney and Hinault, 2021 ; Jauny et al, 2022 ). Indeed, maintenance was observed with preserved dynamics in the relative absence of integrity loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptomatically at the behavioral level and neurologically, Mild Cognitive Impairment (MCI) and dementias of various types associate similarly, the main differences relating to progression rate, pervasiveness, severity and specificity of cognitive impairments and neurological damage as well as the potential for various bio/neuro-markers for (predictive) diagnosis. Among other ways, normal CA and related clinical pathologies can be assessed at the level of functional neural connectivity, the integrated relationship between separated brain regions, as measured by Resting State EEG/ MEG (RS-EEG; Babiloni et al, 2018;Fleck et al, 2017) and/or on-task performance with EEG/MEG (Jauny et al, 2022;Miraglia et al, 2017;Polich, 1997). For example, in older age, greater mean coherence (neural connectivity) in RS-EEG at the individual level correlates with higher levels of cognitive/brain reserves (Fleck et al, 2017).…”
Section: Can Bilingualism Play In This Space?mentioning
confidence: 99%